Гніздування великого кроншнепа (Numenius arquata) на Нижньодніпровській піщаній арені - Петрович, З.О.; Редінов, К.О. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 2011)
На Нижнеднепровской песчаной арене (Северо-Западное Причерноморье, Украина) большой кроншнеп (Numenius arquata) встречается круглогодично, но на гнездовании его не находили. В 2008 г. поселение больших кроншнепов найдено между с. Казачьи Лагеря и с. Новая Маячка Цюрупинского р-на Херсонской области. В 2010 г. там гнездилось до 15 пар. Найдено два гнезда с кладками по 4 яйца: 26.04 и 14.05. In the sand area of the Lower Dnieper (North-West Black Sea area, Ukraine) the Eurasian Curlew (Numenius arquata) occurs throughout a year, but was not discovered on breeding. In 2008, a settlement of Eurasian Curlews was found between the village Kazachi Laheri and the village Nova Mayachka of Tsiurupinsk district of Kherson region. In 2010 there nested up to 15 pairs. There were found two nests with clutches of 4 eggs in each: 26.04 and 14.05.